The falcon$1 (Bs featherss - Roy, Ron, 1940-; Gurney, John Steven, 1962- (New York : Random House, 1998)
Josh and his two friends look for the person who stole a peregrine falcon from its nest.
"A Stepping Stone book."
"Grades 2-4"--cover [4].
Keywords: Peregrine falcon -- Fiction; Falcons -- Fiction; Mystery and detective stories